Appetites and identities : an introduction to the social anthropology of Western Europe - Delamont, Sara, 1947- (Routledge, 1995)
Provides an introduction to the social anthropology of Western Europe. It covers food, migration, politics, urban and country life, magic, religion, sex and language in an accessible fashion, introducing the student to aspects of the anthropology of contemporary European culture.